Bird species - main carriers of influenza type a virus in Eastern Siberia - A. P. Savchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The grand-scale laboratory investigation on finding influenza type A virus in wild and synanthropic birds on vast territories of Eastern Siberia was conducted for the first time. Alongside with the ornithological investigations, we also conducted collection of over 17,000 samples of laboratory investigations of 165 bird species. In the south of Central Siberia in 2006-2011, the antibodies to antihemagglutination were found in 484 samples, 179 out of which were from synanthropic birds. During the investigation of PCR of RNA avian influenza 167 samples were isolated, 17 (10,2 %) out of which were from synanthropic species. In 2014, antibodies were isolated from 30 species, RNA avian influenza were isolated from 26 species of the following bird orders: Podicipediformes - 3/1 (in hemagglutination-inhibition reaction/polymerase chain reaction) of species, Ciconiiformes - 0/1, Anseriformes - 12/10, Gruiformes - 1/1, Charadriiformes - 7/4, Passeriformes - 6/8. In the following years the participation in epizootic process of new species/ subspecies were increased. The maximum virus carriage (40.2 %) and birds infection takes place during the period from July 15 till August 28, which is characterized mainly by the presence of a large number of multipleaged young-of-the-year water fowls on the ponds and riparian vegetation. In the process of work, there was compiled not only the list of species/subspecies of avian influenza virus carriers and vectors, but also revealed their connection with wintering areas and the main location of the recombinant subtypes of highly pathogenic virus H5N1. The cases of virus spreading and its influence on the birds of various ecologic groups were described.